A multiwavelength view of BL Lac neutrino candidates. Issue 2 (10th November 2018) - Righi, C; Tavecchio, F; Pacciani, L
ABSTRACT: The discovery of high-energy astrophysical neutrinos by IceCube kicked off a new line of research to identify the electromagnetic counterparts producing these neutrinos. Among the extragalactic sources, blazars are promising candidate neutrino emitters. Their structure, with a relativistic jet pointing to the Earth, offers a natural accelerator of particles and for this reason a perfect birthplace of high-energy neutrinos. A good characterization of the spectral energy distribution (SED) of blazars can improve the understanding of their physical composition and the emission processes involved. Starting from our previous works, we select those BL Lacs in spatial correlation with IceCube events. We obtain a sample of seven sources and we start an observational campaign to have a better characterization of the synchrotron peak. During our analysis a new source, namely TXS0506+056, has been added because of its position inside the angular uncertainty of a muon track event detected by IceCube. TXS0506+056 was in a high state during the neutrino event and we will consider it as a benchmark to check the properties of the other sources of the sample during the related neutrino detection. We obtain a better characterization of the SED for the sources of our sample. A prospective extreme blazar, a very peculiar low synchrotron peak source with a large separation of the two peaks, and a twin of TXS0506+056 come up. We also provide the γ-ray light curve to check the trend of the sources around the neutrino detection but no clear patterns are in common among the sources.